BOCHA PARALYMPICS: DESIGN FOR PARENTS AND PROFESSIONALS (Fiep Bulletin - online, 2015)
Through the partnership IFSULDEMINAS Campus Muzambinho and the Association of Parents and Friends of Exceptional Guaxupé-MG (APAE), we sought to understand the concept of parents (group A) and professionals (group B) in relation to the Project Initiation Adapted Sports Southeast of Minas Gerais, where their children / students / patients with cerebral palsy, practice Paralympic boccia since February 2014. Through this work we emphasize the importance of family and the multidisciplinary team to encourage their children / students / patients to participate both the project in question, as in other activities involving sport, whether it be practiced in a playful manner or aspect of self performance ..we used qualitative research method with structured questionnaires for each group, where we got very positive responses, which led us the conclusion that everyone has an expanded conception of the project. We stress that it is important that kind of exchange between all involved in the project, so we can enhances it, and expand it in the future.
Keywords: ParalympicBoccia; design; parents and professionals.